Miocene palynology and geochemistry of the Upper Bhuban Formation at Chumukedima, Nagaland (India). Issue 2 (15th February 2022) - Raghumani Singh, Yengkhom; Singh, Wahengbam Ajoykumar; Singh, Shoujaijam Priyokumar; Devi, Mayanglabam Sapana; Devi, Thiyam Priyashwori; Abbott, Mark B.; Guruaribam, Venus; Kilong, Lalminthang
Abstract : In this study, we analysed a rich Miocene palynological assemblage from the Upper Bhuban Formation consisting of 21 genera and 25 species of fungal remains; spores and pollen grains, along with reworked Permian palynomorphs. The latter form a relatively high abundance throughout the studied section. The abundant Hammenisporis spp. with fungal remains and geochemical data of clay minerals in the section imply that a warm and humid freshwater with oxic to anoxic continental or near‐shore depositional environment and tropical–subtropical climatic conditions prevailed during the course of sedimentation of the Upper Bhuban Formation. Geochemical studies of four selected Bhuban shale samples have been analysed for major oxide, trace elements, and rare earth elements (REE) and infer a felsic igneous rock under an active continental margin setting, with a moderate chemical to an intense chemical degree of weathering. The Rock‐Eval pyrolysis results suggest that the organic matter composition is primarily type‐III kerogen, with mixed immature and mature hydrocarbon and gas potential. Abstract : View of geological map, sample locality, and palynological assemblage indicating paleoecology.